PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV PADA MATA PELAJARAN IPA MATERI MENCANGKOK DI SEKOLAH DASAR - Apriani, Luh; Arnyana, Ida Bagus Putu; Suastra, I Wayan (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
The aim of the research is to increase science learning outcomes and improve the learning process by modifying the learning pattern which has so far only been monotonous classroom learning with lectures into independent learning based on student initiative using the demonstration method at class IV on grafting material. The research method is Classroom Action Research (CAR), with the research subjects being 28 class IV students at Mataram 4 State Elementary School. Data collection instrumentation is tests and analysis techniques using interactive analysis techniques. From the results of this classroom action research, it can be concluded that learning science on grafting material using demonstration method at class IV can improve student learning outcomes and can process. It is proven by the results of student learning outcomes, it can be seen that the average achievement value in cycle 1 it was 51.79 then in cycle 2 it increased to 73.57.